Global IR and Western Dominance: Moving Forward or Eurocentric Entrapment?. (September 2019) - Fonseca, Melody
Over the last decade, a call for decolonisation has challenged IR scholarship. The call has advocated for the need to decolonise the epistemology and ontology of the discipline, critically engaging with the legacies of imperialism, colonialism, racism, and patriarchy in global power relations. Parallel to the decolonial project, a call to globalise International Relations has been made by well-known scholars in recent years predominantly through the Global IR project. In this review essay of four books I briefly engage with the debates around Global IR and its critics drawing on a decolonial perspective. On the one hand, I discuss the potentialities and limitations of historiographical deconstruction as a methodological tool, raising issues with the current silencing of the 'present' due to the continued coloniality of knowledge. On the other hand, I delve into the wide range of possibilities that a serious and critical commitment to diversifying the discipline of IR might bring to academics in the so-called non-West/Global South. I analyse current critiques of Global IR considering them necessary though, in some cases, agents for the reification and silencing of the interests of the non-West/Global South. I argue that, whilst coloniality operates in multiple ways, decoloniality is also a project that surpasses the ideal total exteriority as imagined through the West/non-West dichotomy. Relaciones Internacionales Globales y Dominación Occidental: ¿Avance o entrampamiento eurocéntrico?